Association Between Self-Reported Sleep and Cognitive Function in Patients With Mild Cognitive Impairment - Bae, Heewon; Kim, Seonjeong; Choo, Yi-Seul; Joo, Eun Yeon (Journal of sleep medicine, 2024)
Objectives: This study aimed to investigate the association between self-reported sleep and cognitive function in individuals with mild cognitive impairment (MCI) to understand potential implications for Alzheimer’s disease prevention.Methods: This retrospective cohort study included 80 patients with MCI and 70 controls. Participants completed standardized questionnaires to assess self-reported sleep quality (Korean version of the Pittsburgh Sleep Quality Index [PSQI-K]), daytime sleepiness (Epworth Sleepiness Scale [ESS]), and insomnia severity (Insomnia Severity Index [ISI]). Cognitive function was evaluated using the Seoul Neuropsychological Test and the Korean version of the Mini-Mental State Examination. The Korea Instrumental Activities of Daily Living Scale was used to assess instrumental activities of daily living. Correlation analyses examined the relationship between sleep-related parameters and cognitive function.Results: The results indicated no significant differences in PSQI-K and ESS scores between patients with MCI and the control group. Correlation analyses revealed that poorer sleep quality was associated with reduced frontal and executive functions in patients with MCI, particularly in tests such as Controlled Oral Word Association Test (supermarket, -0.311, p<0.001) and Trail Making Test (TMT) B (0.232, p<0.001). Additionally, daytime dysfunction was associated with poorer cognitive performance across language and executive domains (e.g., Korean Boston Naming Test: -0.290, p<0.001; TMTA: 0.248, p<0.001). In both groups, ISI scores were linked to cognitive functions, particularly in attention, phonemic fluency, and executive function (e.g., digit span, backward: -0.225, p<0.01; TMTA: 0.327, p<0.01).Conclusions: These findings suggest that sleep disturbances significantly impact cognitive function and daily living abilities in patients with MCI.